Inducing Paranoia is Linked to Increased Resting Amygdala Cerebral Blood Flow in Healthy Individuals. Issue 3 (29th September 2022) - Pinkham, Amy; Bass, Emily; Klein, Hans; Springfield, Cassi; Kent, Jerillyn; Aslan, Sina
Among individuals with schizophrenia, paranoia has been linked to increased resting cerebral blood flow (CBF) in amygdala, suggesting that amygdala hyperactivity may be a mechanism for paranoid ideation. The present study tested this possible mechanism by assessing whether experimentally inducing paranoia in non-clinical, healthy participants resulted in increased amygdala CBF. Sixty-three undergraduates completed initial measurements of paranoia and resting CBF, via pseudo-continuous arterial spin labeling (pCASL) imaging, and were then randomly assigned to either a paranoia induction ( n = 32) or control ( n = 31) condition before completing a second pCASL scan and another paranoia assessment. Following the induction procedure, individuals in the paranoia induction condition reported fewer positive perceptions of others and greater state anxiety. Resting relative CBF values extracted from right amygdala also demonstrated an increase in CBF over time for individuals in the paranoia induction condition but a decrease in CBF over time for individuals in the control condition. Left amygdala showed no significant effects. These results support the idea that increased resting activity of the amygdala may be a neurobiological mechanism for paranoia.